Analisis Pengaruh Posisi Side hull terhadap Karakteristik Rolling Motion dengan Metode Trochoidal Curve pada Kapal Trimaran - Wilma Amiruddin; Hartono Yudo (Diponegoro University, 2023)
Modifying a fishing boat into a trimaran will expand the ship's deck. In this modification process, the position of the side hull will influence the rolling motion characteristics of the ship. The objective of this study is to see the probability of synchronism. Synchronism is a situation that can cause a large forced oscillation. Two ship models are analyzed, the ship model 1 (12 x 10) and the ship model 2 (10 x 12). The analysis was carried out based on hydrostatic calculations using Delftship and energy changes with the Trochoidal Curve theory approach. The analysis results show that all models have a high probability of synchronization conditions. The position of the side hull does not significantly affect the model for fixed displacement. Ship model 1 has a period (T) of 2.4 s, and ship model 2 has a period (T) of 2 s. This value is relatively low compared to the value of the rolling period of the monohull, where the period (T) is 6 s and the minimum limit for fishing vessels (T) is 5.5 s. This change produces a significant rolling motion transverse.